Laser versus dissection technique of tonsillectomy - Wan Leman, Wan Ishlah; Fahmi, A. M.; Srinovianti, N. (Malaysian Medical Association, 2005)
Tonsillectomy is the single most common operation performed in Ear, Nose and Throat Department. Various methods of tonsillectomy have been practiced over the century aimed at reducing or eliminating intraoperative and postoperative morbidity. Due to various blood supplies received, intraoperative bleeding is the most difficult problem and securing it is time-consuming. The time taken to control the bleeding would invariably determine the length of operation. Common postoperative complications are bleeding and pain. This study evaluated the operative time, intraoperative blood loss, postoperative pain and other postoperative complications of tonsillectomy performed by laser as compared to conventional dissection technique. This is a prospective randomized study whereby sixty patients were divided into two groups of equal number. In one group, the tonsillectomy performed by laser and in the other group the tonsillectomy performed by conventional dissection technique. Operative time and amount of blood loss is significantly reduced in the laser group. Total postoperative pain and post operative complications were not significantly different between the two groups. Tonsillectomy by using laser have shown less intraoperative bleeding and shortened the operative time. In the hospital where laser machine and expertise are available, it is justifiable to use this technique as effective method of performing tonsillectomy.